Gun violence prevention policy: Perceived and actual levels of gun owner support - Kathleen L. Grene; Amani S. Dharani; Michael B. Siegel (Preventive Medicine Reports, 2023)
Gun violence prevention is often viewed as polarizing, although gun owners actually support many gun safety policies. The aim of this paper was to investigate the relationship between gun owners' perceptions of other gun owners' support for gun policies and their own individual support for such policies. NORC at the University of Chicago, which uses a panel of adults recruited through probability sampling, conducted an online/phone survey of 1,078 adult gun owners. Respondents were asked about their individual support for seven gun safety policies and their perceptions of other gun owners’ support for those policies. We used two-sample t-tests and multivariate logistic regression analyses to explore the relationship between perceived and individual support.We found that gun owners underestimated fellow gun owners’ support for gun violence prevention policy, especially if they personally opposed that policy. Gun owners’ perception of fellow gun owners’ support for a policy was significantly associated with the likelihood of individual support for that policy for all laws examined. These findings have important implications for correcting misperceptions of the level of gun owner support for gun safety policies as well as conducting and targeting educational campaigns to respond to and correct media misinformation.